Current Situation and Causes of School Bullying among Adolescents - He, Wenjing (International Journal of Social Sciences and Public Administration, 2024)
In recent years, there has been an increasing number of school bullying incidents in China. Compared with the previous bullies directly beating and abusing classmates, the current form of school bullying is a new form-cyber bullying. Teenagers have various forms of school bullying, and cause great harm, which is not only physical harm but also psychological harm, seriously harm the mental health of teenagers. What reason is worth thinking about.